New Labour in power : precedents and prospects - Brivati, Brian; Bale, Tim, 1965- (Routledge, 1997)
Combines historical, political and practical approaches to the questions raised by the election victory. Includes much-needed analysis of the current state of the party and invaluable insight into the context of longer term trends.